Monitoring Model of Concrete Dam Deformation Based on Gray Wolf Optimization Algorithm - CHEN Shuyun; ZHOU Wenzhong; GU Yanchang; WANG Hong (Renmin Zhujiang)
Dam deformation is one of the most reliable indicators that can reflect the actual condition of concrete dam.Modeling and analysis of dam deformation monitoring data is an effective way to reflect the operation behavior of concrete dam and seek for the internal law of deformation.In addition,the mathematical model can be applied to predict the deformation.In order to improve the accuracy of modeling and deformation prediction,this paper proposes a deformation monitoring model of concrete dam based on gray wolf optimization algorithm,applies the model to the engineering examples and compares the results with that from the statistical model established by the conventional stepwise regression method and the BP-neural network.The results show that the monitoring model based on the gray wolf optimization algorithm has higher accuracy and better prediction effect.Therefore,the gray wolf algorithm is superior in establishing deformation model,which provides a new reference for deformation analysis and prediction of concrete dam.